Sosialisasi dengan Tema Peta Jalan Sukses Strategi Orang Tua dalam Mengembangkan Potensi Anak Usia Dini PAUD Nur Hidayah Cibomo Desa Bendung Kecamatan Kasemen: Pengabdian - Dira Rizki Amalia; Siti Muawanah; Riski Wulandari; Munawaroh (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service activity aims to provide parents with understanding and skills in designing effective strategies to develop the potential of early childhood, especially at PAUD Nur Hidayah Cibomo, Bendung Village, Kasemen District. Through a socialization with the theme "Roadmap for Successful Parental Strategies in Developing the Potential of Early Childhood," participants were given material on the importance of the role of parents as the first and primary educators, methods of stimulating child development appropriate to their stages, and how to build a conducive learning environment at home. The implementation methods of the activity included interactive lectures, group discussions, and simulations of positive parenting practices. The results of the activity showed an increase in parental knowledge and awareness regarding strategies for developing children's potential, as seen from the enthusiasm of the participants and their commitment to implementing the methods they had learned. This activity is expected to be the first step in building synergy between schools, parents, and the community in creating a generation of intelligent, creative, and characterful early childhood children.